Formation of students’ communication skills using the “Dailo” interactive dialogue system based on artificial intelligence technologies - Sofya I. Dreytser (RUDN Journal of Informatization in Education)
Problem statement. Pedagogical technologies for the communication skills formation are constantly being improved, new methods and practices are emerging to solve this problem. The use of information technology to develop professional communication skills presents particular interest. However, today there is not enough data on what specific tools there are in the field of information technology for the formation of communication skills, how exactly communication skills are formed with the help of information technology, and through what mechanisms the formative effect occurs. An approach to informatization of education based on artificial intelligence tools used to develop professional communication skills among employees of large companies is discussed. Methodology. The author analyzes the capabilities of interactive dialogue systems, implemented using artificial intelligence technologies, for the formation of professional communication skills. Communication scenarios with different behavioral possibilities for the participant and criteria for control assessment of the communication skills of the participants were developed. The experimental study was carried out as part of the activities of the company's personnel training departments. The participants of the experiment were 35 employees of large companies. Statistical processing of the results was performed using the Mann - Whitney and Pearson tests. Results. It was confirmed that the dialogue simulator teaches the ability of flexible reproduction and improvisation in the process of dialogue while maintaining its logic and essence. In the second experiment, the data obtained partially confirm this hypothesis and give rise to a new assumption that the tool can be used to diagnose defining reflection by providing participants with overspecified and underspecified tasks. Conclusion . The experiment data suggest that the dialogue simulator enhances flexible dialogue skills while maintaining logic. Additionally, it may help diagnose reflection by presenting tasks of varying determinacy. These hypotheses require further investigation to guide future research on artificial intelligence in education.